1998
DOI: 10.1093/ajcp/110.1.43
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Trial of a Prototype Telepathology System Featuring Static Imaging With Discrete Control of the Remote Microscope

Abstract: A b s t r a c t Routine diagnosis of pathology images transmitted over telecommunications lines remains an elusive goal. Part of the resistance stems from the difficulty of enabling image selection by the remote pathologist. To address this problem, a telepathology microscope system (TelePath, TeleMedicine Solutions, Birmingham, Ala) Increasingly in medicine, electronic images are replacing film-based media. Radiology, remains the one medical specialty that routinely uses electronic images for diagnosis.1-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Oberholzer et al [20] report a slightly higher sensitivity (85.7%) than was found in our study. Eide and Nordrum [6] and Nordrum and Eide [17] found similar values to ours, with, in particular, a test accuracy of 89.0% (11/100 misclassifications, 1 false-positive, 3 false-negative and 7 deferred diagnoses); Winokour et al [33], a test accuracy of 96.9% (routine diagnoses without frozen section situation); Steffen et al [27] found 89%; Fujita et al [9], 94.9% and Adachi et al [1], 93.2%. Our data are in the range of those reported above and reach a test efficiency of 90%, with deferred diagnoses excluded, and 81% if deferred diagnoses are included.…”
Section: Discussionsupporting
confidence: 86%
“…Oberholzer et al [20] report a slightly higher sensitivity (85.7%) than was found in our study. Eide and Nordrum [6] and Nordrum and Eide [17] found similar values to ours, with, in particular, a test accuracy of 89.0% (11/100 misclassifications, 1 false-positive, 3 false-negative and 7 deferred diagnoses); Winokour et al [33], a test accuracy of 96.9% (routine diagnoses without frozen section situation); Steffen et al [27] found 89%; Fujita et al [9], 94.9% and Adachi et al [1], 93.2%. Our data are in the range of those reported above and reach a test efficiency of 90%, with deferred diagnoses excluded, and 81% if deferred diagnoses are included.…”
Section: Discussionsupporting
confidence: 86%
“…It is interesting that no false-positive diagnosis of malignancy was rendered by the tele-Francis/Junaid/Dajani pathologist in frozen as well as paraffin sections. Such a telediagnosis of frozen sections has been successfully reported by several experts with a diagnostic accuracy ranging from 89 to 96.9% [8,[17][18][19].…”
Section: Discussionmentioning
confidence: 92%
“…Thus, this mode was abandoned (Weinstein, unpublished observations, 1988) [56,78]. Currently, the designation "dynamic-robotic" is used exclusively in the context of real-time video imaging.…”
Section: Static Image Telepathologymentioning
confidence: 99%